Analysis of Law Enforcement Regarding Fault in Defamation Crimes Through Electronic Media - Diah Pudjiastuti; Sahat Maruli Tua Situmeang (Humanities, Society, and Community, 2026)
This research investigates the enforcement of defamation laws in electronic media, focusing on the interpretation of "intentional" and "unauthorized" elements under Law No. 1 of 2024, which amends Law No. 11 of 2008 on Electronic Information and Transactions (ITE Law). The urgency of this study arises from legal ambiguities and the rising number of online defamation cases, highlighting inconsistencies in judicial interpretations and enforcement challenges. Using a normative juridical approach, this study analyzes statutory provisions, jurisprudence, and fault theory to assess the practical application of defamation laws. The findings reveal a lack of uniformity in judicial decisions, emphasizing the need for clearer definitions and standardized legal interpretations. This study underscores the necessity of refining existing legal provisions to enhance legal certainty and the effectiveness of enforcement. Practical implications include increasing public legal awareness of responsible digital communication and implementing preventive measures against cyber defamation. To address legal gaps, this research recommends legislative reforms to clarify legal definitions, promote alternative dispute resolution mechanisms, and strengthen law enforcement training, ensuring a balance between legal protection and freedom of expression in the digital era.